MASS-CULTURE: DALAM DIALEKTIKA DENGAN MUSIK KITA - Kusnendi, Cecep (LP2M ISBI Bandung, 2017)
The development of music in Indonesia today are quite encouraging quantity, but the quality is very doubtful. The phenomenon is predicted as a result of the spread of mass-culture which have an impact on the proliferation of kitsch in our music.In our music kitsch showed in repetitive forms, sensational, sensual, sentimentality, vulgar, glamour, eroticism, sex, etc. These forms mainly seen in the lyrics, singer's body movements, stage costumes, and so many repetitions songs sold in the market. The conditions in the realms of our music, is motivated by a variety problems such as economics which resulted the artist (composers) should follow the mass-culture tasted. The other sad phenomenon also seen in the lack of infrastructure for the art trainings, also in adequate number of music critics. Now, the growth and development of the diatonic and pentatonic's music in our country, showed